Acquiring Syntactic Variability: The Production of Wh-Questions in Children and Adults Speaking Akan - Omane, Paul Okyere; Höhle, Barbara (Frontiers in Communication, 2021)
This paper investigates the predictions of the Derivational Complexity Hypothesis by studying the acquisition of wh-questions in 4- and 5-year-old Akan-speaking children in an experimental approach using an elicited production and an elicited imitation task. Akan has two types of wh-question structures (wh-in-situ and wh-ex-situ questions), which allows an investigation of children’s acquisition of these two question structures and their preferences for one or the other. Our results show that adults prefer to use wh-ex-situ questions over wh-in-situ questions. The results from the children show that both age groups have the two question structures in their linguistic repertoire. However, they differ in their preferences in usage in the elicited production task: while the 5-year-olds preferred the wh-in-situ structure over the wh-ex-situ structure, the 4-year-olds showed a selective preference for the wh-in-situ structure in who-questions. These findings suggest a developmental change in wh-question preferences in Akan-learning children between 4 and 5 years of age with a so far unobserved u-shaped developmental pattern. In the elicited imitation task, all groups showed a strong tendency to maintain the structure of in-situ and ex-situ questions in repeating grammatical questions. When repairing ungrammatical ex-situ questions, structural changes to grammatical in-situ questions were hardly observed but the insertion of missing morphemes while keeping the ex-situ structure. Together, our findings provide only partial support for the Derivational Complexity Hypothesis.